Synthesis, HOMO-LUMO Analysis and Antioxidant Activity of Novel Tetrazole Hybrids - Murthy, S.N.; Johar, K.; Manoj Kumar, B.V.; Satish, V.A.N.; Emmanuel, K.A. (Акад. Е.А. Бөкетов ат. Қарағанды ун-ті КЕАҚ баспасы, 2023)
In this work a series of twelve tetrazole hybrids 7a-l were prepared via Cu promoted regioselective Narylation, C-N bond formation reactions and assed for in vitro anti-oxidant activity. Spectroscopic methods like 1H NMR, 13C NMR, IR, and LCMS were used for the characterization of the obtained compounds and all data were in good agreement with the expected structures. Next, to study the chemical reactivity, the HOMOLUMO energies and their energy gap, hardness, softness, chemical potential of the synthesized chemical compounds 7a-j were calculated by B3LYP/6-31g(d, p) method using Gaussian 09 package. Сompounds 7d, 7e, 7j have demonstrated the lowest HOMO-LUMO energy gap (4.7856eV, 4.7905eV, 4.89009eV), and the lowest chemical potential (-3.07254eV, -3.06173eV, -3.0166eV) values, also the highest chemical softness (0.41792eV, 0.41749eV,0.40899eV), and the lowest chemical hardness (2.3928eV, 2.3952eV, 2.44504eV) values, which may correspond to higher chemical reactivity compared with other compounds of this series. Moreover, obtained compounds 7a-l were screened in vitro for the antioxidant activity by DPPH radical scavenging method. The screening results revealed that compounds 7d, 7e and 7k are the most potent among all the examined compounds, and the remaining compounds have moderate activity.
Keywords: Tetrazole; Morpholine; Cu catalyst; Regio-selectivity; anti-oxidant activity; DPPH; Gaussian 09; DFT; HOMO-LUMO analysis